SPE Hydrocarbon Economics and Evaluation Symposium 1999
DOI: 10.2118/52942-ms
|View full text |Cite
|
Sign up to set email alerts
|

National Health, Wealth, and Energy Use

Abstract: This paper was prepared for presentation at the 1999 SPE Hydrocarbon Economics and Evaluation Symposium held in Dallas, Texas, 20-23 March 1999.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Pro-oil research established a correlation between oil prices and misery (and the more common idea of wealth and energy consumption per capita) (Skov, 1999).…”
Section: Correlationsmentioning
confidence: 99%
“…Pro-oil research established a correlation between oil prices and misery (and the more common idea of wealth and energy consumption per capita) (Skov, 1999).…”
Section: Correlationsmentioning
confidence: 99%
“…Like most high income developed countries, the US has benefited from availability of low cost oil and gas energy in the last century 11 . The US GDP has grown from $822 bn (1996 chained $) in 1929 to $9,440 in 2002, an average overall real growth rate of 3.4%/yr for 73 years, through booms and busts, recessions, and wars.…”
Section: Us Economic and Physical Well Beingmentioning
confidence: 99%
“…Studies have shown that energy consumption is positively correlated to quality of life 12,18 , with quality of life measured by such factors as infant mortality, literacy, life expectation, and university attendance. Cassedy and Grossman 7 provide a good discussion of two diametrically opposed ethical positions that apply to the global distribution of energy (pages 123-130 in Ref.…”
Section: Changing Industry Policymentioning
confidence: 99%